Corruption in India: PIL as a restraint - Panda, Snehalata (2011)
In India quite a few instiutional mechanisms are available to deal with corruption. Among serveral options, Public Interst Litigation (PIL) caters to this obligation of the people to initiate action against person who use their position and power to their self advantage. It is an invalueable option to check corruption, raise consciousness and restrain people in power and authority to misues the onerous duty of serving people. The article discusses demand and supply side of corruption, importance of PIL as a useful tool to restrain corruption though not eliminnating it altogether, its deficiencies and suggests approaches to make it more effective. - Reproduced.
Keywords: Corruption - India; Corruption